La Création de réseaux dédiés à l’enseignement design‑build : mise en place, objectifs, enjeux depuis 2012 - Coline Madelaine (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article looks at the development of international networks of teachers offering new ways of learning architecture through design-build and live project pedagogies throughout the 2010s. It presents the conditions in which these networks emerged, namely the designbuildXchange and the Live Projects Network, by tracing their history. It then goes on to examine the reasons for their emergence and the issues they currently face, in an approach that is both critical and forward-looking. The aim is to understand their position in relation to architectural education, which they seek to renew.